Coalition for Security? The SADC Security Community and Lesotho´s Coalition Government - Moyo, Sibusiso (2015)
Lesotho's 2012 elections resulted in the formation of a coalition government. Idealy the formation of a coalition government is accompanied by positive expectation of compromise and development. However, a turn of events in Lesotho's coalition government has threatened the stability of that country. This article examines the dynamics of security and insecurity in Lesotho's coalition government. The point of departure is an overview of security in Southern Africa in order to define security in the context of the SADC security community. The paper discusses South Africa-Lesotho relations highlighting the interdependence between the two countries. An evaluation of the efficacy of Lesotho's coalition government and the impact of the coalition on Lesotho's security is made in this paper. The article identifies factionalism, a strong military insubordination and power struggles as contributing factors towards the 2014 crisis in Lesotho. Resumo As eleições de Lesoto em 2012 resultaram na formação de um governo de coligação. Idealmente, a formação de um governo de coligação é acompanhada por uma expectativa positiva de compromisso e desenvolvimento. No entanto, uma série de acontecimentos no governo de coligação do Lesoto ameaçou a estabilidade desse país. Este artigo examina a dinâmica de segurança e insegurança no governo de coligação do Lesoto. O ponto de partida é uma visão geral da segurança na África Austral, a fim de definir a segurança no contexto da comunidade de segurança da SADC. Este documento discute as relações África do Sul-Lesoto, destacando a interdependência entre os dois países. Uma avaliação da eficácia do governo de coligação do Lesoto e o impacto da coligação na segurança do Lesoto é feita neste documento. O artigo identifica facciosismo, uma forte insubordinação militar e lutas pelo poder como fatores que contribuem para a crise de 2014 no Lesoto.